Effect of soil preparation techniques on the biochemical properties and microbial communities of a citrus orchard after replanting and conversion into organic management - Pérez-Piqueres, Ana; Albiach, Remedios; Domínguez, Alfons; Canet, Rodolfo (2018)
Adequate levels of organic matter and biological activity in soil under organic management are key for crop nutrition and protection against soil-borne pathogens. Before replanting, soil must therefore be prepared accordingly. In this study, the effects of commonly used techniques (vegetal cover, organic amendment, solarization and organic amendment + solarization) on the main biochemical properties and microbial communities of a replanted organic citrus soil were investigated during a full season. The results clearly showed negative solarization effects that degraded the soil organic matrix by the moisture and heat combination, which affected all enzyme activities, save chitinase. These effects were particularly severe and long-lasting for ammonium oxidation-related activities and communities. Solarization was also the main factor to affect soil microbial communities, although differences between treatments disappeared in 6 months, save Bacillus-like bacteria. Given that nutrient cycling is essential for fertilisation in organic cropping, caution must be taken when considering the use of solarization to reduce pathogens from soil.